2013
DOI: 10.1158/1940-6207.capr-12-0484
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Putative Immunologic Targets for Colon Cancer Prevention Based on Conserved Gene Upregulation from Preinvasive to Malignant Lesions

Abstract: The length of time required for pre-invasive adenoma (AD) to progress to carcinoma, the immunogenicity of colorectal cancer (CRC), and the identification of high risk populations make development and testing of a prophylactic vaccine for the prevention of CRC possible. We hypothesized that genes upregulated in AD relative to normal tissue, which maintained increased expression in CRC, would encode proteins suitable as putative targets for immunoprevention. We evaluated existing AD and CRC microarray datasets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…They identified 23 genes whose proteins were already reported to be overexpressed in colon adenoma and CRC. To determine whether these proteins could be targets of immunosurveillance, they examined sera from early stage CRC patients and controls and found significantly elevated IgG against several of the molecules [30]. The same group has tested in mouse models the ability of vaccines based on non-mutated tumor antigens to prevent cancer.…”
Section: Candidate Antigens For Preventative Vaccinesmentioning
confidence: 99%
“…They identified 23 genes whose proteins were already reported to be overexpressed in colon adenoma and CRC. To determine whether these proteins could be targets of immunosurveillance, they examined sera from early stage CRC patients and controls and found significantly elevated IgG against several of the molecules [30]. The same group has tested in mouse models the ability of vaccines based on non-mutated tumor antigens to prevent cancer.…”
Section: Candidate Antigens For Preventative Vaccinesmentioning
confidence: 99%
“…Abnormally glycosylated MUC1 has also been found on breast ductal carcinomas in situ , as well as adenoma of the colon, a precursor to colon cancer (Ajioka, Watanabe, & Jass, 1997; Mommers et al, 1999). Recent studies to find new antigens expressed on cancer stem cells and premalignant lesions looking at colon adenoma and colorectal cancer microarrays identified 160 up-regulated genes compared to normal colon (Broussard et al, 2013). In another study researchers found that a multi-partite vaccine targeting three antigens on pre-invasive breast disease (Neu, IGFBP2, IGF-IR) could prevent breast cancer in a spontaneous mouse tumor model in which mice were treated after developing premalignant lesions (Disis et al, 2013).…”
Section: Prophylactic Cancer Vaccinesmentioning
confidence: 99%
“…Preclinical studies demonstrate that multi-antigen vaccines are more effective than single antigen vaccines by inducing immunity to more antigens, generating more activated T-cells homing to the premalignant lesion (68). A multi-antigen vaccine for colon cancer, targeting several immunogenic proteins that are upregulated in adenomas and conserved through carcinoma [69], is moving towards the clinic. Preliminary studies of single antigen vaccines are encouraging in reducing polyp formation in AOM-treated mice and APC min-mice (personal communication ML Disis).…”
Section: Immunopreventionmentioning
confidence: 99%